Enhancing Senior High School Students' Listening Skills Through the Implementation of the VoA (Voice of America) Learning English Application - Naomi Dalila Malau; Agus Widyantoro; Sunusi Dauda (International Journal of Multilingual Education and Applied Linguistics, 2025)
This study aims to improve high school students' listening skills through the application of Voice of America (VoA) Learning English. Using a classroom action research (CAR) approach in two cycles at a high school in Yogyakarta with 36 students, this study assessed listening skills before and after using the application. Data were collected through pre-tests, post-tests, observations, and interviews, and analyzed using an interactive model and SPSS. The results show that the use of VoA Learning English improves students' listening skills, motivation, and engagement, while also proving the effectiveness of technology-assisted learning through authentic listening materials. This study recommends the integration of digital media in teaching English listening skills.